Time trends in the burden of non-COVID-19 lower respiratory tract infections among children aged 0 to 14 years - Lu, Weihong; Guo, Xixia; Ren, Yishuai; Wang, Li; Xu, Tingting; Xu, Yali; Li, Duoduo; Cai, Nali; Li, Shujun; Zhang, Xingliang; Li, Haibin; Wu, Xiangtao (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aims to analyze the global burden, temporal trends, and main pathogenic characteristics of pediatric lower respiratory tract infections(LRTIs) across different age groups.MethodsThis repeated cross-sectional study included children with LRTIs aged 0–14 years from 204 countries and regions from 1990 to 2021. The primary outcomes were cases and rates of incidence, disability-adjusted life years (DALYs), mortality, and their trends associated with LRTIs. Estimates were generated using the DisMod-MR 2.1 tool.ResultsIn 2021, neonates had the highest incidence and mortality. From 1990 to 2021, the global mortality rate of LRTIs in children decreased by 76.8%, with the reduction primarily driven by a 79.1% decrease in children aged 2–4 years. However, in low-middle SDI regions, the mortality rate remained as high as 4502.003 per 100,000. The primary pathogens contributing to LRTI-related DALYs and deaths in most age groups were Streptococcus pneumoniae, Staphylococcus aureus, and Klebsiella pneumoniae, while among newborns, the leading pathogens were Klebsiella pneumoniae, Group B Streptococcus, and Acinetobacter baumannii. BAPC predicted a slight improvement in the mortality rates from 18 LRTI pathogens over the next decade; however, influenza may cause an increase in childhood mortality reaching 44,820 deaths per 100,000 by 2031.ConclusionsThe burden of LRTIs remains significant in low- and middle-income countries, as well as among neonates and females. While the burden of various pathogens is gradually declining, influenza warrants particular attention. Expanding vaccine coverage, improving sanitary conditions, and early interventions for high-risk children are crucial strategies to reduce LRTI burden.